PEMIKIRAN HASAN TIRO TENTANG NEGARA DAN PENGARUHNYA TERHADAP PEMBENTUKAN GERAKAN ACEH MERDEKA TAHUN 1976-2005 - reka umi jaya (SWADESI: Jurnal Pendidikan dan Ilmu Sejarah, 2021)
ABSTRACT : The process of forming Hasan Tiro's thoughts about the state is based on historical awareness and the injustice of the central government (Jakarta) towards Aceh. This study aims to examine Hasan Tiro's thoughts about the state and its influence on the formation of the Free Aceh Movement. This study uses historical methods which include heuristics, source criticism, interpretation, and historiography. Based on the results of this study, it can be concluded that, according to Hasan Tiro, the appropriate country for the Indonesian archipelago, including Aceh, is an Islamic federation state. The factors that influence Hasan Tiro's thoughts about the state are education, politics, socio-culture, economy, and the history of Aceh's sovereignty. As for the influence of Hasan Tiro's thoughts on the state and its influence on the formation of GAM, namely, the ideals of establishing an Islamic state, the ideals of establishing Aceh's autonomy and resistance to the central government (Jakarta).  Keywords: Thought, Hasan Tiro, State, GAM